Mathematics for Business, Finance and Economics - Wilkes F.M (Rouledge, 1994)
A thorough introduction to mathematical concepts and methods used in the analysis of business management, finance and economics. Preface, Introduction, Straight Lines and Linear Equations, Linear Inequalities, Functions and Turning Points, Slopes and Derivatives and Turning Points, Functions of More than One Variable, Constrained Optimization with Lagrange Multipliers, Integration, Exponential and Logarithmic Functions, Matrices, Appendix: Optimization: Further Considerations, Index.